ANALYSIS OF THE QUANTITY OF EXHAUST GASES EMITTED FROM VEHICLES IN A CROSS SECTION THROUGH COMPUTER SIMULATION PROGRAM - Ikromov Akmaljon Gofurjonovich; Makhmudov Galib Nasimdjanovich; Usmonov Zafar Tursunovich; Abdurakhimov Lochinbek Xayitbekovich (Web of Journals Publishing, 2023)
This paper presents the results of the development of a model of the intersection using the PTV VISSIM simulation software. One of the problematic intersections in the city of Tashkent was selected and the traffic flow during peak hours was studied to analyze the intersection. The article discusses two solutions to reduce the amount of toxic gases and fuel consumption. The first solution is by optimizing the traffic light phases and changing their control cycle. The second solution represents a reduction by changing the geometric parameters of the intersection. After we applied both solutions, the service level of the intersection, LOS, increased from F to B.
Keywords: intersection model, simulation software, traffic flow, rush hour, toxic gases, fuel consumption, regulatory phase, regulatory cycle, intersection service level.